(untitled) (Journal of Medicine, 2014)
Background: Non-alcoholic fatty liver disease (NAFLD) is becoming a public health problem with increasing incidence and it has been shown to be associated with diabetes, dyslipidemia, obesity and metabolic syndrome and ultimately puts more than half the worlds population at risk of developing NAFLD/NASH/cirrhosis in the coming decades. The importance of detection of patients with NAFLD is to intervene the associated factors and avoid transformation to more severe forms of the disease. Methods: An observational case control study was carried out at Medicine Department, Dhaka Medical College Hospital (DMCH), Dhaka, during the period of August, 2011 to June, 2012. A total number of 100 consecutive patients and 100 healthy controls was approaches DMCH were enrolled in this study. Out of 100 NAFLD patients only 20 patients gave consent for liver biopsy to see the extent of liver damage. Result: Less physical activity, Obesity, mean blood pressure, Diabetes, TG, TC were significantly (P<0.05) higher in NAFLD. Metabolic syndrome was 64% in NAFLD. According to NASH Activity Scoring system definite NASH (score >5) was found in 9(45%) of the NAFLD group. Conclusion: Significant proportion of NAFLD patient suffers from NASH which is alarming and they have potential for the development of advanced liver disease. So recognition of these risk factors in patients of NAFLD can help in early implementation of strategies that halt the progression of this disease. DOI: http://dx.doi.org/10.3329/jom.v14i2.19665 J Medicine 2013, 14(2): 143-148